2012
DOI: 10.1155/2012/908314
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in HIV Infection: Can Immunotherapy Regulate the Regulator?

Abstract: Regulatory T cells (Tregs) have a dominant role in self-tolerance and control of autoimmune diseases. These cells also play a pivotal role in chronic viral infections and cancer by limiting immune activation and specific immune response. The role of Tregs in HIV pathogenesis remains poorly understood as their function, changes according to the phases of infection. Tregs can suppress anti-HIV specific responses and conversely can have a beneficial role by reducing the deleterious impact of immune activation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 129 publications
3
49
0
3
Order By: Relevance
“…The Th17/Treg balance plays a dominant role in the maintenance of mucosal immunity [9,16]. These cells are derived from common progenitor cells and their differentiation pathways are reciprocally modulated upon immune activation during HIV-1 infection, resulting in bacterial translocation [9,18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Th17/Treg balance plays a dominant role in the maintenance of mucosal immunity [9,16]. These cells are derived from common progenitor cells and their differentiation pathways are reciprocally modulated upon immune activation during HIV-1 infection, resulting in bacterial translocation [9,18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Among T-cell subsets, regulatory T-cells (Tregs), play a pivotal role in peripheral tolerance and pathogenesis of cancer and chronic viral infections [16]. Indeed, Tregs were shown to suppress effector T-cells activation and function [17].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, studies reported that FoxP3 + CD25 + CD4 + Tregs are important neuroprotective immunomodulators in stroke, but their contributive effects towards stroke pathophysiology are still controversial [12, 27, 28]. Although many review articles have focused on FoxP3 + CD25 + CD4 + Tregs [9, 29, 30], a new review is necessary for appraising recent research advances in FoxP3 + CD25 + CD4 + Tregs after stroke. The objectives of this review are (1) survey the evidence of the vital roles played by FoxP3 + CD25 + CD4 + Tregs in stroke pathophysiology, (2) discuss further investigations to fully elucidate the precise regulatory mechanisms of FoxP3 + CD25 + CD4 + Tregs in stroke, and (3) evaluate the possible therapeutic application and potential pitfalls of modulating the activity and quantity of FoxP3 + CD25 + CD4 + Tregs in stroke treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Durante a infecção pelo HIV, a expansão de células Treg poderia ser benéfica por suprimir a ativação generalizada de células T, ou poderia ser prejudicial por suprimir o impacto deletério causado pela ativação de respostas imunes anti-HIV e assim contribuindo com a persistência viral (Chevalier, Weiss, 2013;Jenabian et al, 2012;Sunder et al, 2012). Células dendríticas possuem um papel crucial na resposta imune ao HIV, pois são essenciais na indução de respostas HIV-específicas por meio da ativação de linfócitos T auxiliares CD4+, que uma vez ativados auxiliam as DCs na ativação de linfócitos T citotóxicos CD8+ (CTL) capazes de controlar a replicação viral (Banchereau et al, 2000;Day, Walker, 2003;Hugues, 2004;Letvin, Walker, 2003 Com base nisso, podemos sugerir que em nosso protocolo, a substituição da IL-4 pelo IFN-α, apenas, ainda não seja o suficiente para potencializar a habilidade das MoDCs em promover uma resposta imune antiviral mais eficaz.…”
Section: Discussionunclassified